Genetic Variation of I/D Enzyme Converting Angiotensin (ACE) with Athlete Muscle Resistance - Indriono Hadi; Lilin Rosyanti (Humanistic Network for Science and Technology (HNST), 2019)
Programmed physical exercise in athletes causes the cardiovascular system to be more efficient in pumping blood and carrying oxygen to muscles. Indicators of cardiovascular changes during exercise are: oxygen consumption, heart rate, stroke volume, differences in arterial and venous oxygen, blood pressure and blood flow. Some physical components that need to be considered for development include: VO2 max, muscle endurance, strength, flexibility, speed, stamina, agility, and explosive power. Some specific genes are identified as a muscle phenotype response to strength training, namely angiotensin-converting enzyme (ACE), which converts angiotensin I to angiotensin II. The insertion / deletion (I/D) polymorphism in this gene was found to play a role in variations in the activity of the ACE enzyme, in someone carrying a deletion allele (D) who had higher ACE enzyme activity. The research was carried out at the Organization of the Indonesian National Sports Committee (KONI), especially in South Sulawesi Bangkit athletes. The results showed a significant relationship between genetic variation in ACE gene (I/D) with muscle endurance (p-value 0.05). Likewise in sprints and endurance sports, there was no relationship with variations in the ACE gene (p-value >0.05). In conclusion, further research should be on athletes who win the Olympics or World Championships, with a single sports discipline, larger sample sizes and more diverse genetic variations, so that the ACE genotype can be explored and developed in athletes. Keywords: Athlete, Physical exercise, ACE gene, Genetic variation of I / D, Muscle endurance